OPTIMIZATION OF SOWING STRUCTURE ON FAMILY FARMS UNDER UNSTABLE BUSINESS CONDITIONS - Todorović, Saša; P. Muncan, Mihajlo (Economics of Agriculture, 2009)
Agricultural producers are currently facing with a large number of challenges that significantly influence their business activities. This fact must be accepted, and producers have to be properly prepared for the new business conditions. According to that its the time that many of them asked how the current situation is reflected in their farms and what to do in the future. Bearing this in mind, a family farm model was used for optimization of sowing structure under unstable business conditions and to detect the most significant factors influencing this process. The presented results of this study suggest that is possible to eliminate limitation in their operations and increase profitability.